Strategic and statistical analysis of regional socio-economic development in the conditions of the digital environment - V. Aleshnikova; T. Burtseva; H. Shadiev; A. Gubareva (Управление)
Тhe creation and development of the digital economy in the regions of Russia is a new factor in their socio-economic development. This should be reflected in near future in the strategies of socio-economic development of regions. In the Russian Federation, at present, for developing and evaluating the implementation of the socio-economic development strategy of the region, a universal methodology has not been developed, and the standard approaches for implementing strategic planning have been adapted from the management of corporate structures.The purpose of the article is to test the methodology of statistical evaluation of the socio-economic development of the region in the digital environment. The methodological basis of the study are: the general statistical method of dynamic standards, index and coefficient analysis, the method of pairwise comparisons. The scientific novelty of the presented results are the author’s methodological developments: the system of indicators of the socio-economic development of the region in the digital environment and the regulatory assessment model. The practical significance of the research results lies in the possibility of applying the author’s assessment methodology for monitoring regional development strategies.The creation of integral statistical measures (models) for monitoring traditional and new factors of the region’s development will provide solutions to their quantitative assessment, allow clarify both the planning and implementation stages of the region’s shortcomings and problems, ensure the implementation of the principle of integrated socioeconomic development of the region, contribute to enhancing the consistency of the objectives of regional development strategies, it will allow diagnostics of the development of the digital economy and develop new strategic orientations at the regional level, which in turn will make it possible to develop organizational mechanisms for involving people in the region in resolving issues of territorial strategic development.